PENGARUH SUBSTITUSI PROTEIN TEPUNG PUCUK INDOGOFERA ZOLLINGERIANA DENGAN PROTEIN BUNGKIL KEDELAI DALAM RANSUM TERHADAP ORGAN DALAM BROILER - Melia Afnida Yanti (Universitas Muhammadiyah Tapanuli Selatan, 2018)
This research aimed to see the effect of Indigofera Zollingeriana top leaf meal as substitution of soybean meal in the diets on development giblets of broiler chickens. The study was conducted for 35 days and giblets sampling was carried out on the 35 day. The DOC used is the cobs strain produced by PT. Charoen Pokphan Indonesia with an average weight of 35.1 grams. A completely randomized design (CRD) with four treatments and four replications and ten birds in each replication was used in this experiment. Dietary treatments were: R1= diet containing 20% soybean meal without I. zollingeriana top leaf meal ; R2= diet containing 16% soybean meal and 5.9% Indigofera Zollingeriana top leaf meal (substitute 20% soybean meal protein with Indigofera Zollingeriana top leaf meal) ; R3= diet containing 12% soybean meal and 11.8% Indigofera Zollingeriana top leaf meal (substitute 40% soybean meal protein with Indigofera Zollingeriana top leaf meal); R4= diet containing 8% soybean meal and 17.74% Indigofera Zollingeriana top leaf meal (substitute 20% soybean meal protein with Indigofera Zollingeriana top leaf meal). Variable measured was giblet of broiler (liver, heart, gizzard, spleen, bile, pancreas, kidney, relative length of small intestine and cecum.). The result showed that usage Indigofera Zollingeriana top leaf meal in the diets did not affect giblets of broiler chickens. The conclusion of this study was Indigofera Zollingeriana top leaf meal can be use up to 17.74% to substitute 60% soybean meal protein without interrupting the development giblets of broiler.Key words: Broiler Chicken; Indigofera Zollingeriana top leaf meal; Blood profile.